DAMPAK PENGGUNAAN TEKNOLOGI BERBASIS APLIKASI PADA USAHA RESTORAN BERSKALA MIKRO & KECIL - Michael Christian (Journal of Business & Applied Management, 2019)
ABSTRACTData from the Ministry of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia of micro and small businesses in 2016-2017 shows an increasing number. This increase explained that public interest in making businesses, especially with small-scale businesses, was still very high in Indonesia. Emerging restaurants with new concepts as a result of growing food and beverage trends such as sharing economy that maximizes Communication Information Technology (ICT) in the form of applications helped shape the increase in the food business in Indonesia. Several studies have explained the relationship between the use of Information Technology to business performance. This study aims to analyze the impact of the use of application-based information technology on business performance. This research is a quantitative study with a Partial Least Square model and uses SMART PLS 3.0. Using 98 micro and small restaurant businesses in the North Jakarta region, the results of this study explain that restaurant business performance is influenced the application-based technology. Then business performance is also influenced by market orientation. Indirectly there is a market orientation role that also contributes to the use of application-based technology on restaurant business performance. The suggestion for the next research is to be able to measure the quality of restaurant information delivery from the operating system of the application used. In addition, the background of business actors is suggested to need to be studied along with the shift of the generation.Keywords: business performance, information communication technology, orientation. ABSTRAKData dari Kementerian Koperasi dan Usaha Kecil dan Menengah Republik Indonesia usaha mikro dan kecil tahun 2016-2017 menunjukkan angka yang meningkat. Kenaikan ini menjelaskan bahwa minat masyarakat dalam membuat usaha terutama dengan skala usaha kecil masih sangat tinggi di Indonesia. Bermunculan restoran dengan konsep baru sebagai akibat dari tren makanan dan minuman yang terus berkembang seperti sharing economy yang memaksimalkan Teknologi Informasi Komunikasi (TIK) dalam bentuk aplikasi turut membentuk peningkatan bisnis makanan di Indonesia. Beberapa penelitian telah menjelaskan keterkaitan antara penggunaan Teknologi Informasi terhadap kinerja usaha. Penelitian ini bertujuan untuk menganalisis dampak penggunaan teknologi informasi berbasis aplikasi pada kinerja usaha. Penelitian ini adalah penelitian kuantitatif dengan model Partial Least Square dan menggunakan SMART PLS 3.0. Menggunakan 98 usaha restoran mikro dan kecil di wilayah bagian Jakarta Utara, hasil penelitian ini menjelaskan bahwa kinerja usaha restoran dipengaruhi oleh penggunaan teknologi berbasis aplikasi. Kemudian kinerja usaha juga dipengaruhi oleh orientasi pasar. Secara tidak langsung terdapat peran orientasi pasar yang turut memberikan pengaruh penggunaan teknologi berbasisaplikasi pada kinerja usaha restoran. Saran bagi penelitian berikutnya adalah dapat mengukur kualitas penyampaian informasi restoran dari system operasional aplikasi yang digunakan. Selain itu, latar belakang pelaku usaha disarankan perlu dikaji seiring dengan bergesernya generasi pelaku usaha.Kata kunci: kinerja usaha, teknologi informasi komunikasi, orientasi.